Visualization of Collagen–Mineral Arrangement Using Atom Probe Tomography. Issue 9 (23rd July 2021) - Lee, Bryan E. J.; Langelier, Brian; Grandfield, Kathryn
Abstract: Bone is a functional material comprised of mainly two phases: an organic collagenous phase and an inorganic mineral phase. Collagen–mineral arrangement has implications for bone function, aging, and disease. However, theories on collagen‐mineral arrangement have been confined to studies with low spatial and/or compositional resolution resulting in an extensive debate over the location of mineral with respect to collagen. Herein, a strategy is developed to extract a single mineralized collagen fibril from bone and analyze its composition and structure atom‐by‐atom with 3D sub‐nanometer accuracy and compositional clarity using atom probe tomography (APT). It is shown for the first time a method to probe fibril‐level mineralization and collagen–mineral arrangement from an in vivo system with both the spatial and compositional precision required to comment on nanoscale collagen–mineral arrangement. APT of leporine bone shows distinct and helical collagen fibrils with mineralized deposits both encapsulating and incorporated into the collagenous structures. This study demonstrates a novel fibril‐level detection method that can be used to probe the composition of bone and contribute new insights to the structure and organization of mineralized materials such as bones and teeth. Abstract : The compositional organization of bone and the arrangement of its two major components, mineral and collagen, with respect to each other is a subject of great debate. This study provides the first example of collagen fibrils being probed with sub‐nanometer accuracy and demonstrates that mineral is deposited both within the collagen fibrils while also encapsulating them.